A review on topology and control strategies of high-power inverters in large- scale photovoltaic power plants - Amirreza Azizi; Mahdi Akhbari; Saeed Danyali; Zahra Tohidinejad; Mohammadamin Shirkhani (Heliyon)
In recent years, there has been a substantial growth in renewable energy sources and among these sources, solar energy is known as one of the best energies. The increasing adoption of solar energy across various applications underscores its significance in the renewable energy landscape. The integration of large-scale photovoltaic power plants into the primary power grid necessitates efficient and reliable power conversion processes, particularly as there is a growing demand for enhanced controllability and flexibility from the grid side. Power electronic converters, bolstered by advancements in control and information technologies, play a pivotal role in facilitating large-scale power generation from solar energy. High-power multilevel inverters have emerged as a compelling solution for addressing the escalating energy requirements. This paper aims to delve into the exploration of diverse structural configurations and technical hurdles encountered in high-power multilevel inverter topologies, alongside the associated control systems and modulation techniques tailored for application in large-scale photovoltaic power plants (LS-PV-PP) systems. A comprehensive analysis of high-power multilevel inverter topologies within solar PV systems is presented herein. Subsequently, an exhaustive examination of the control methods and strategies employed in high-power multilevel inverter systems is conducted, with a comparative evaluation against alternative approaches. Lastly, the paper delves into a discussion on prominent modulation methods utilized in multilevel power inverters, assessing their performance characteristics in various operational scenarios.